Language, Aggression, and Self-Regulation in Young Children. (September 2021) - Clark, Robert; Menna, Rosanne; McAndrew, Annamaria J.; Johnson, Emily M.
Aggression in early childhood has been found to predict negative outcomes later in life, including delinquency and psychopathology. The present study explored associations between young children's language, self-regulation, and physical aggression. A community sample of 126 preschool children aged 3 to 6 years ( M = 4.87 years, SD = 0.87; 59% boys) and their mothers participated in the study. Children's physical aggression and self-regulation were measured by the parents' report. Children completed measures of intelligence and language. Their language abilities negatively predicted physical aggression. Children's self-regulation—specifically, inhibitory self-control and emergent metacognition—mediated the relationship between language and physical aggression. The results suggest that, among young children, physical aggression is related to an understanding of language meaning and how that understanding is used to interpret and communicate. The specific language delays implicated may lead to physical aggression through a lag in inhibitory self-control and emergent metacognition. Implications of these findings for assessment and early intervention are highlighted.